2008
DOI: 10.1182/blood-2007-09-114371
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy and reduced toxicity of multifactorial adjuvants compared with unitary adjuvants as cancer vaccines

Abstract: Identification of Toll-like receptors (TLRs)and their ligands, and tumor necrosis factor-tumor necrosis factor receptor (TNF-TNFR) pairs have provided the first logical, hypothesis-based strategies to molecularly concoct adjuvants to elicit potent cell-mediated immunity via activation of innate and adaptive immunity. However, isolated activation of one immune pathway in the absence of others can be toxic, ineffective, and detrimental to long-term, protective immunity. Effective engineered vaccines must include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 44 publications
(61 reference statements)
5
64
0
Order By: Relevance
“…Attempts to use DC-based vaccines to mount a strong Ag-specific immune response against tumorassociated Ags or pathogenic agents, which elude the human immune system, rely on the use of adjuvants. Various TLR ligands have been used with some success as adjuvants in DCbased vaccines against tumor-associated Ags (35)(36)(37)(38). The present findings offer the tantalizing possibility that knockdown of ILT3 could be used as an adjuvant itself to improve the effectiveness of DC based vaccines to generate immunogenic responses against tumor Ags or chronic pathogenic infections.…”
Section: Discussionmentioning
confidence: 93%
“…Attempts to use DC-based vaccines to mount a strong Ag-specific immune response against tumorassociated Ags or pathogenic agents, which elude the human immune system, rely on the use of adjuvants. Various TLR ligands have been used with some success as adjuvants in DCbased vaccines against tumor-associated Ags (35)(36)(37)(38). The present findings offer the tantalizing possibility that knockdown of ILT3 could be used as an adjuvant itself to improve the effectiveness of DC based vaccines to generate immunogenic responses against tumor Ags or chronic pathogenic infections.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies that describe the use of anti-CD40 Ab as an immunotherapy against tumors conclude that monotherapy is not sufficient for tumor eradication but this treatment has to be combined with cytokines, TLR ligand signaling, or chemotherapy (13)(14)(15)39). We agree that anti-CD40 Ab monotherapy, as described in this study, is not always capable of tumor eradication and that the use of combinatorial treatments will be beneficial, and propose that our superior administration method (i.e., delivery of a low-dose agonistic CD40 Ab in a slow-release formulation in the tumor-draining area) is also valuable when combining anti-CD40 Ab treatment with other agents.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we determined the effect of microbial/inflammatory agents on PKCθ -/-2C T cell expansion. Recent studies indicate that a combination of TLR ligands and agonistic anti-CD40 Abs (FGK45) provide an exceptionally strong signal for T cell proliferation (40)(41)(42). Furthermore, studies have shown that TLR ligands can exacerbate GVHD (43).…”
Section: Essential Requirement For Pkcθ In 2c T Cell Expansion and Cymentioning
confidence: 99%